360-Degree Perspectives on Obesity - Magdalena Cuciureanu; Cătălin-Cezar Caratașu; Levon Gabrielian; Otilia Elena Frăsinariu; Laura Elisabeta Checheriță; Laura Mihaela Trandafir; Gabriela Dumitrița Stanciu; Andrei Szilagyi; Ina Pogonea; Gabriela Bordeianu; Radu Petru Soroceanu; Călin Vasile Andrițoiu; et al. (Medicina, 2023)
Alarming statistics show that the number of people affected by excessive weight has surpassed 2 billion, representing approximately 30% of the world’s population. The aim of this review is to provide a comprehensive overview of one of the most serious public health problems, considering that obesity requires an integrative approach that takes into account its complex etiology, including genetic, environmental, and lifestyle factors. Only an understanding of the connections between the many contributors to obesity and the synergy between treatment interventions can ensure satisfactory outcomes in reducing obesity. Mechanisms such as oxidative stress, chronic inflammation, and dysbiosis play a crucial role in the pathogenesis of obesity and its associated complications. Compounding factors such as the deleterious effects of stress, the novel challenge posed by the obesogenic digital (food) environment, and the stigma associated with obesity should not be overlooked. Preclinical research in animal models has been instrumental in elucidating these mechanisms, and translation into clinical practice has provided promising therapeutic options, including epigenetic approaches, pharmacotherapy, and bariatric surgery. However, more studies are necessary to discover new compounds that target key metabolic pathways, innovative ways to deliver the drugs, the optimal combinations of lifestyle interventions with allopathic treatments, and, last but not least, emerging biological markers for effective monitoring. With each passing day, the obesity crisis tightens its grip, threatening not only individual lives but also burdening healthcare systems and societies at large. It is high time we took action as we confront the urgent imperative to address this escalating global health challenge head-on.